Development administration. IN Documents [column] (1977)
The attainment of an effective system for development administration is necessary to support the achievement of national goals and objectives. During the 10-year period (1978-87), a continuing program for increasing administrative capability through dynamic flexibility and self-reliance will be formulated and implemented. While the following are likely developments in the future based on recent policy pronouncements, the final outcome of events will depend largely on basic political decisions which are beyond the terms of reference of this chapter.
Keywords: Public administration; Decentralization; Regional planning